2017
DOI: 10.1088/1742-6596/896/1/012114
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of the formability of AA6013-T6

Abstract: Abstract. AA6013 is an age-hardenable, aluminum alloy with the potential for structural applications in weight-sensitive automotive components. The alloy is at peak strength in the T6 temper, but exhibits relatively low room temperature formability. In an effort to avoid costly post-forming heat-treatments, warm forming of the AA6013 in the T6 temper is investigated in the current work. The experimental formability of the alloy is characterized from room temperature to 250°C through limiting dome height (LDH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Formability characterization of the PA, T6 and T76 tempers was undertaken at room temperature (23°C), 150°C, 175°C and 200°C. Testing was accomplished using a double-acting hydraulic press with tooling heated by closed-loop controlled embedded heater cartridges, as described in [9] and [17]. The specimens were heated in-situ, with typical heating curves measured at the specimen flanges plotted in Figure 2c).…”
Section: Limiting Dome Height Testing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Formability characterization of the PA, T6 and T76 tempers was undertaken at room temperature (23°C), 150°C, 175°C and 200°C. Testing was accomplished using a double-acting hydraulic press with tooling heated by closed-loop controlled embedded heater cartridges, as described in [9] and [17]. The specimens were heated in-situ, with typical heating curves measured at the specimen flanges plotted in Figure 2c).…”
Section: Limiting Dome Height Testing and Analysismentioning
confidence: 99%
“…Necking is assumed to have initiated once changes in the surface curvature occur due to initiation of an acute neck. The curvature approach applied in this work is termed the Enhanced Curvature Method (ECM) and was built upon the method developed by DiCecco et al [9], [17]. For comparison purposes, limit strains are also computed using the ISO12004:2-2008 methodology.…”
Section: Limiting Dome Height Testing and Analysismentioning
confidence: 99%
“…Warm forming technology is a promising approach to improve the formability of peak-aged 7075 aluminum alloys (AA7075-T6) [6][7][8][9], where the AA7075-T6 blank is heated to target temperatures followed by warm forming with heated or cold dies. The formability of aluminum alloys under warm conditions can be evaluated by forming limit curves (FLCs) [10,11]. Sotirov et al [12] obtained temperature-dependent forming limits of EN AW-7075-T6 using the Nakazima tests and found that the major strain of FLC raised from 0.15 to 0.3 at plane strain condition as the temperature increased from room temperature to 230 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Warm forming technology is a promising approach to improve the formability of peak-aged 7075 aluminum alloys (AA7075-T6) [5][6][7][8], where the AA7075-T6 blank is heated to target temperatures followed by warm forming with heated or cold dies. The formability of AA7075-T6 under warm conditions can be evaluated by forming limit curves (FLCs) [9][10]. Sotirov et al [11] obtained temperature-dependent forming limits of EN AW-7075-T6 using the Nakazima tests and found that the major strain of FLC raised from 0.15 to 0.3 at plane strain condition as the temperature increased from room temperature to 230℃.…”
Section: Introductionmentioning
confidence: 99%